Vascularization is delayed in long nerve constructs compared with nerve grafts. Issue 2 (27th May 2016) - Farber, Scott J.; Hoben, Gwendolyn M.; Hunter, Daniel A.; Yan, Ying; Johnson, Philip J.; Mackinnon, Susan E.; Wood, Matthew D.
ABSTRACT: Introduction : Nerve regeneration across nerve constructs, such as acellular nerve allografts (ANAs), is inferior to nerve auto/isografts especially in the case of long defect lengths. Vascularization may contribute to poor regeneration. The time course of vascular perfusion within long grafts and constructs was tracked to determine vascularization. Methods : Male Lewis rat sciatic nerves were transected and repaired with 6 cm isografts or ANAs. At variable days following grafting, animals were perfused with Evans Blue albumin, and grafts were evaluated for vascular perfusion by a blinded observer. Results : Vascularization at mid‐graft was re‐established within 3–4 days in 6 cm isografts, while it was established after 10 days in 6 cm ANAs. Conclusions : Vascular perfusion is reestablished over a shorter time course in long isografts when compared with long ANAs. The differences in vascularization of long ANAs compared with auto/isografts suggest regenerative outcomes across ANAs could be affected by vascularization rates. Muscle Nerve 54 : 319–321, 2016